KADAR TGF-β1 PLASMA DAN LIMFOSIT-T CD4+DI PENDERITA YANG TERINFEKSI HIV STADIUM I - Alberthina Alberthina; Endang R; Erwin AT (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
HIV infection and AIDS have been spread throughout the world and the number of patients continues to increase from year to year.Indonesia is one of the countries with quite a high increase in the incidence of HIV and AIDS. The absolute number of CD4+T-lymphocytesand percentage in HIV-infected patients can be used to determine the stage of the disease, and progression of the disease, as well as topredict the onset of the opportunistic diseases. In certain circumstances sometimes it is difficult to determine clinically and the results ofthe absolute number of CD4+ T-lymphocytes and its percentage are still high. So the examination of TGF-β1 is necessary for predictingthe disease course in the patient, because the increase of the disease progress is also accompanied by the increased levels of TGF-β1. Thepurpose of this study is to know and to prove the existence of the correlation between plasma levels of TGF-β1 and the absolute numberpercentage of CD4+T-lymphocytes in stage I HIV-infected patients. The research was carried out by a Cross sectional observational study,the samples were derived from 41 stage I HIV-infected patients treated at the Outpatient Clinic of the Infectious Disease IntermediateCare Unit (UPIPI) in the Dr. Soetomo Hospital from January to May 2012. The examination of TGF-β1 plasma was performed by ELISAmethod, the number of absolute and percentage of CD4+T-lymphocyte were counted by immuno flowcytometry (BD FACSCalibur™). Theresults were statistically analyzed using a Pearson product moment correlation test. It was shown that the TGF-β1 plasma levels in stageI HIV-infected patients tended to increase, as well as the number and percentage of CD4+ T-lymphocytes which were also increased. Theresult of this study revealed that the number of CD4+T-lymphocytes which were less absolute and more than 200 cells /μL showed nocorrelation with the plasma levels of TGF-β1 in stage I HIV infected patients. However, there was a significant positive correlation betweenthe number of CD4+T-lymphocytes percentage with TGF-β1 plasma in stage I HIV infection.